TANGGUNG JAWAB PERDATA DOKTER KEPADA PASIEN DALAM TRANSAKSI TERAPEUTIK - Hadi Setiawan, Made; Dharma Kusuma, A.A.Gede Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 02, Januari 2015)
This paper titled Civil Responsibility Doctors To Patients In teraupetikTransaction. This paper on the background of the background by the practice oftherapeutic transactions performed by physicians and patients. This paper also aims todetermine the responsibility of the doctor to the patient in the therapeutic transaction.In the writing of normative legal research methods to approach legislation. which canpull in this paper is the therapeutic transaction between doctor and patient in thechapters set in the Transaction Therapeutic Responsibility Doctors can generally bedivided into 3 namely liability for losses caused by (1) Unlawful acts (Article 1365 ofthe Civil Code), (2) Negligent or inadvertent (Article 1366 Civil Code), (3)Responsibility of superiors to subordinates (Article 1367 Civil Code), and added withnumber.36 Act of 2009 on health, article 56 paragraph 1, 2, 3, article 57 paragraph 1,2, article 58 paragraph 1, 2, 3.
Keywords: Responsibility, Doctor, Patient, Therapeutic Transactions